Профілактика ротації торичних інтраокулярних лінз після факоемульсифікації катаракти з використанням стандартного капсульного кільця - Завгородня, Наталія Григорівна; Новікова, Валерія Юріївна; Цибульська, Таміла Євгенівна; Zavhorodnia, N. G.; Novikova, V. Yu.; Tsybulska, T. Ye. (My University, 2021)
Мета: оцінити ефективність використання розробленого способу профілактики ротації ТІОЛ після факоемульсифікації катаракти на очах з рогівковим астигматизмом. Rotation of TIOL after phacoemulsification of cataracts is accompanied by a significant decrease in visual acuity and requires repositioning of IOL. We have developed a method of preventing TIOL rotation by using a standard capsule ring. Aim: to evaluate the effectiveness of using the developed method of prevention of TIOL rotation after phacoemulsification of cataracts in the eyes with corneal astigmatism. Results: We examined 46 patients (59 eyes) who underwent phacoemulsification and implanted TIOL. Rotation of TIOL 6 months after surgery in the control group with 22 eyes (70.9%), in the main group - with 12 eyes (42.85%). In the main group in all cases, the deviation of the TIOL axis did not exceed 6 degrees. Conclusions. The proposed method of prevention of rotation of TIOL allows to increase the efficiency of phacoemulsification of cataracts in the eyes with corneal astigmatism, provides a stable result of visual functions.
Prevention of toric intraocular lens rotation after cataract phacoemulsification using a standard capsule ring